If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 2a = 28 Reorder the terms: 2a + 3b = 28 Solving 2a + 3b = 28 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 2a + 3b + -3b = 28 + -3b Combine like terms: 3b + -3b = 0 2a + 0 = 28 + -3b 2a = 28 + -3b Divide each side by '2'. a = 14 + -1.5b Simplifying a = 14 + -1.5b
| 6+2c=14 | | 4x-4x-x=16-1 | | 8.50y+16=94 | | 15+b=1.5(b+2) | | -6(4x+10)=5-11x | | 8=-(x+3)+3 | | 4/5×15=30 | | 2524=5g+389 | | 6=b+4-4 | | 9y^2-18y+25x^2+100x-116=0 | | 4u/9=8 | | 112+1.25g=867 | | -6(4x+0)=5-11x | | 2=2x+1+9 | | -15-(-2-20)=x | | 3v=15/2 | | -6log(n-10)=-12 | | 4(x+5)-6=4x+14 | | 1025v+2.456=7583 | | 7-9p=7-9p | | 15x=1000 | | 7x-21=4x+2 | | 4-2.2h=-3.7 | | 11k+1.5=249 | | 3/4y-1=2 | | 3p+3s=2 | | -6x+3+x=-47 | | 5+2=100 | | .89=in(x) | | (1/2)x^(5/2)=16 | | x+(x*3)=240 | | 7-4x-7x=-4 |